Ethanolic Extract of Ganoderma mexicanum Pat. Mycelium: A Source of Bioactive Compounds with Antiproliferative Activity and Potential PPAR-γ Natural Ligands - Lucia T. Angulo-Sanchez; Max Vidal-Gutiérrez; Heriberto Torres-Moreno; Martín Esqueda; Aldo Gutiérrez; Georgina Vargas; Juan Luis Monribot-Villanueva; José A. Guerrero-Analco; César Muñoz-Bacasehua; Ramón Enrique Robles-Zepeda (Pharmaceuticals)
Background/Objective: Ganoderma spp. have long been studied for their bioactive pharmacological properties, and their biomass and extracts have been obtained from various sources. This study adopts a novel approach: enriching a liquid culture of Ganoderma mexicanum with a vineyard pruning waste extract to identify bioactive compounds with antiproliferative activity through enriched chromatographic fractions. Methods: The ethanolic extract from a mycelial culture was separated following a partitioning process, and the hexane fraction was subsequently separated in a chromatographic column. The fractions were evaluated for their antiproliferative properties against cancer cell lines. The interactions of the molecules identified with peroxisome proliferator-activated receptor gamma (PPAR-γ) were analyzed via molecular docking. Results: Three chromatographic fractions (FH11–FH13) exhibited antiproliferative activity which was significantly more effective against non-small lung cancer cells (A549). The cells treated with the crude extract and fractions presented a balloon-like morphology. A chemical analysis of the active fractions allowed us to identify four compounds: one fatty acid (9-Hydroxy-10E,12Z-octadecadienoic acid) and three triterpenes (ganoderic acids DM, TQ, and X). These compounds showed interactions with the PPAR-γ receptor through molecular docking. Conclusions: Ganoderma mexicanum is a promising source of compounds with antiproliferative activity that could serve as natural ligands for PPAR-γ and has possible applications in lung cancer therapy.